Institutional Transformation of Ukraine's Agricultural Sector - Tetiana Zinchuk; Nataliia Kutsmus; Oleksandr Kovalchuk; Vitalii Dankevych; Tetiana Usiuk (Review of Economic Perspectives, 2017)
The complex analysis of the main stages of Ukraine's agricultural sector development for the independence period has been done in the paper. It was established, that institutional changes in the agricultural sector of economy occurred concerning following institutions: private property, state regulation, pricing, social capital, competition. The peculiarities of land and property private ownership forming as agri-reforms basis have been determined. Post-Soviet institutions destruction caused rapid decrease of economic development and rural population welfare at the first stage of transformations. The main tendencies of agrarian sector functioning under market conditions, providing growth of the agricultural production and export potential of Ukraine have been identified. It was proved, that progressive economic changes did not provide similar results in rural areas development. As a result, the necessity of focusing on humancentric model of rural development was grounded.
Keywords: 330; agriculture; agricultural enterprise; institutions; private household; land; rural development; export potential